Lissa and the fund-raising funk - Jones, Jen (Mankato, Minn Stone Arch Books, 2012)
Lissa Marks is the fund-raising chair for her middle school cheer team, but will her widowed mother be able to afford to keep Lissa on the team?
A gift from book Africa
English Stories
1 2 13 15
NEW_ZTN_GN
Keywords: Cheerleading -- Juvenile fiction; Fund raising -- Juvenile fiction